The Knowledge – Based Economy in the New Members States of the European Union: Methodological Aspects - Wasiak , Mariusz (Comparative Economic Research. Central and Eastern Europe, 2008)
The concept of a knowledge–based economy as developed since the end of the 20th century is no subject to multiple theoretical approaches as well as varied methodological efforts. This has become a starting point for classifying sectors or even entire economies in terms of intensity of impact of knowledge as well as the developing of rankings defining the general position of a country assessed with respect to level of implementation of the knowledge–based economy model. The article presents an overview and classification of research methods in the realm of the knowledge–based economy—OECD, World Bank, and European Union—as well as the results of rankings using the Knowledge Economy Index (World Bank Institute) for the new member states of the European Union.